Proposing multi-item replenishment model for an inventory management system of Malaysia’s SMEs - Salleh, Mohd Rizal; Rahman, Irfan ur; Mohamad, Effendi; Nawaz, Rashid; A Rahman, Muhamad Arfauz (Hashemite University, 2022)
The present study describes a modified Economic Order Quantity (EOQ) for multi-item replenishment model with the deterministic demand nature of an inventory management. The function is subjected to the available financial and space constraints in the organization. If the constraints are not satisfied under the given conditions, then Lagrange technique is applied to obtain the optimal order quantity of the multi-items. The purpose of this study is to empower the manufacturing sector of Malaysia’s SMEs with the advantages of the inventory model that controls the overproduction and underproduction inventories to meet their customer’s demand on the right time. From this study, 90.9% of the optimum quantities of products had been achieved by using the multi-item inventory replenishment model as compared to the EOQ. This model is able to control the total cost of inventory efficiently for the optimum space availability.